Broadband integrated lens for illuminating reflector antenna with constant aperture efficiency - Fernandes, C. A.; Lima, E. B.; Costa, J. R. (IEEE Transactions on Antennas and Propagation, 2010)
A new integrated shaped lens antenna configuration is described with frequency stable radiation pattern and phase center position across a broad 1:3 frequency band, which can be used for focal plane reflector feeding in quasi-optical radio telescope systems. The lens is compatible with the integration of ultrawide-band uniplanar printed feeds at its base and equally broadband mixing devices, like the Hot Electron Bolometer (HEB), although these are not used in the present work. Measurements on a scaled mm-wave lab prototype have confirmed stable performance versus frequency, with only +/- 1 dB directivity variation, and better than 94% Gaussicity, thanks to the possibility to impose a predefined output radiation pattern template. Simulations were performed to test the illumination of an off-set parabolic reflector by the lens radiation pattern, which confirmed reasonably constant aperture efficiency in the order of 78% across the 100% bandwidth.